Crystal structure of tetraaqua(4,4′-bipyridine-N,N′)copper(II) fumarate tetrahydrate, Cu(H2O)4(C10H8N2)(C4H2O4) · 4H2O - Ying E.-B.; Zheng Y.-Q.; Zhou Q.-Q. (Zeitschrift für Kristallographie - New Crystal Structures, 2004)
C14H26CuN2O12, monoclinic, C12/c1 (no. 15), a = 16.631(3) Å, b = 11.155(2) Å, c = 13.096(3) Å, β = 125.08(3)°, V = 1988.3 Å3, Z = 4, Rgt(F) = 0.038, wRref(F2) = 0.094, T = 293 K.